(1183) some experiences, with network schedule modelling of a cement firm-the Toura co. Case بعض التجارب، مع نمذجة جدولة الشبكة لشركة أسمنت طرة. - farahat, ahmed M. (the institute of national planning, 2018)

(untitled)
the last few years have witnessed a large increase in the demand of cement for well known reasons. it is estimated that the size of such demand by the year 1980 will be around 10 million tons. in comparison with the total production capacity of the four current cement mills a noticeable unbalance could be easily detected.